1999
DOI: 10.1097/00005392-199907000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Helical Computerized Tomography Arteriography for Evaluation of Live Renal Donors Undergoing Laparoscopic Nephrectomy

Abstract: Helical CT is highly accurate and specific for the demonstration of renal arterial anatomy. Poor opacification resulted in a lower sensitivity for venous anatomy. Overall, helical CT provides essential anatomical information, and is an alternative to standard urography and arteriography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 11 publications
4
50
1
4
Order By: Relevance
“…Traditionally, renal angiography and excretory urography have been used to evaluate the anatomy of renal arteries and renal function, respectively, in potential kidney donors. However, several studies have shown that helical computed tomography (CT) angiography can replace renal angiography and excretory urography in the evaluation of potential kidney donors (3)(4)(5)(6)(7)(8)(9). Hence, helical CT angiography has become an accepted method for the evaluation of living donors before they undergo laparoscopic nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, renal angiography and excretory urography have been used to evaluate the anatomy of renal arteries and renal function, respectively, in potential kidney donors. However, several studies have shown that helical computed tomography (CT) angiography can replace renal angiography and excretory urography in the evaluation of potential kidney donors (3)(4)(5)(6)(7)(8)(9). Hence, helical CT angiography has become an accepted method for the evaluation of living donors before they undergo laparoscopic nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…At our center, we decide on the side to be donated based on simplicity of vascular anatomy on CT angiography and results of a nuclear medicine renal function scan [3,11]. If decision on side is equivocal, the right side is usually preferred, given the easier mobilization and avoidance of the risk of splenic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) angiography and nuclear imaging were routinely performed [3,11]. Single-vessel anatomy was preferred for donation.…”
Section: Methodsmentioning
confidence: 99%
“…El tiempo que transcurre entre el inicio de la inyección del contraste y la obtención de estas imágenes es de aproximadamente 6 a 8 min. Con equipos de TC multidetector es posible obtener también imáge-nes urográficas en la propia unidad de TC y tienen el potencial de sustituir a la radiología convencional en el estudio de la vía urinaria 22 .…”
Section: Jr Ayuso Et Al/actas Urol Esp 2006; 30 (2): 145-151unclassified